Penguasaan Dan Kepemilikan Hak Atas Tanah Menurut Hukum Adat Larvul Ngabal - Rumaf, Ahmad Muhajir; Matuankotta, Jenny Kristiana; Labetubun, Muchtar Anshary Hamid (Pusat Kajian Pesisir dan Masyarakat Hukum Adat Fakultas Hukum Universitas Pattimura, 2023)
Customary law develops following the development of society and existing folk traditions. Customary law is a deposit of decency in a society whose truth is recognized in that society. Purposes of the research: 1. To find out and analyze how land rights are regulated based on Larvul Ngabal Customary Law. 2. To find out and analyze the obstacles to enforcing Larvul Ngabal customary law. Methods of the research: Normative Juridical Law is used as a type in this study. This type of research in a normative juridical manner conducts studies originating from legal materials, doctrines, principles, legal principles, as well as positive legal provisions that aim to answer the legal issues being studied. Another name for normative research is doctrinal legal research which is commonly called library research because the purpose of this research is written regulations or other legal materials. The results of the study show that the contents of the Larvul Ngabal Law do not specifically regulate the regulation of land rights, control and ownership of land parcels by the Kei indigenous people, which are regulated by each Orong Kai (Head of Ohoi) and Head of Marga based on the regulations in force within the indigenous peoples. . The regulations for each Ohoi regarding land tenure and ownership existed long before the Larvul Ngbal Law existed. Obstacles in upholding larvul Ngabal customary law, namely with the development of the era the habits and understanding of indigenous peoples faded, making it difficult for customary functionaries to apply customary law, apart from that, there was no support from the local government in this matter to form a regional regulation that supports the implementation of the law. customs related to land rights.